PENGARUH KUALITAS PELAYANAN, SARANA PRASARANA, DAN KEPERCAYAAN TERHADAP KEPUASAN MASYARAKAT DALAM BEROBAT DI PUSKESMAS REJOSO, KABUPATEN NGANJUK - Dina Novitasari; Dwi Puji Rahayu; Muhammad Bawono; Muhammad Ali Lutfi (Media Mahardhika, 2026)
This study aims to determine the influence of service quality, facilities and infrastructure, and trust on community satisfaction at Puskesmas Rejoso. Using a quantitative approach with a survey method involving 397 respondents, the data were analyzed using multiple linear regression. The results show that service quality significantly affects community satisfaction with a t-value of 3.010 and a significance level of 0.003; facilities and infrastructure also have a significant effect with a t-value of 1.970 and a significance level of 0.049; and trust significantly influences satisfaction with a t-value of 2.095 and a significance level of 0.037. Simultaneously, the three variables significantly affect satisfaction, indicated by an F-value of 14.654, a significance level of 0.000, and an R Square value of 0.101. These findings indicate that improving service quality, enhancing facilities, and strengthening public trust collectively contribute to increased satisfaction with healthcare services.